Insights into the regulation of hearing regeneration - Khalaily, Lama; Avraham, Karen B. (Frontiers in Audiology and Otology, 2024)
Our perception of sound is mediated by sound-sensitive hair cells in the inner ear, located in a specialized neuro-epithelia that transmits information to the auditory cortex via the auditory pathway. A major cause of hearing loss is damage and death of these sensory hair cells. In humans, hair cells are only generated during embryonic development and cannot be replaced if damaged due to aging, excessive noise, ototoxic drugs, or illness. Much effort is currently being invested worldwide in identifying methods to improve the ability of hair cells to regenerate and circumvent their age-dependent limitations. Compared to numerous studies focused on gene therapy to rescue deafness caused by a specific mutation prior to the onset of hair cell damage, research on auditory epigenetics is relatively recent. Although research indicates that epigenetic alterations play a crucial role in the differentiation, development, and regeneration of auditory hair cells, there is still a dearth of comprehensive knowledge regarding the specific role played by epigenetic modifications in the auditory system, with a particular emphasis on their potential correlation with the function and development of the auditory system. Additionally, these modifications have been linked to the regeneration of hair cells caused by using pharmaceutical inhibitors (e.g., inhibition of Notch) and genetic (e.g., induced Atoh1 expression) treatments, which can lead to hair cell regeneration and restore hearing. Recent developments in targetable epigenome-editing tools, such as CRISPR, and direct reprogramming that enable targeted genome editing. Additionally, the emergence of organoids and epigenetic drugs (Epidrugs) presents novel prospects for hearing restoration through the manipulation of regeneration pathways, making them promising methods for future regenerative treatments for hair cells. The potential of epigenetic modifiers as viable targets for pharmacological manipulation is becoming evident. Future therapies aimed at hair cell regeneration are particularly beneficial, due to the advantageous aspect of restricted drug exposure within the inner ear. KEYWORDS Hair cells, supporting cells, regeneration, epigenetics, Epidrug